SIGNIFYING THE FEMALE’S CHARACTER IN INDIAN FICTION - Adepu Priyanka, Dr. Babina Bohra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The changing status of women over the ages has been documented in literary history. The path that women of yesteryear have trodden has been fraught with critical, contemptuous, and censures, yet they have persevered through it with grace and dignity. Women have ignored the naysayers and continued on their dangerous path. The strong sisterhood of today's women is the product of a long journey. Women are the primal creators. Women are without a doubt the most important contributors to the development of our universe. A woman's unwavering devotion to her family in all her roles as mother, daughter, sister, and wife is a cornerstone of her community. Women's potential as authors, businesswomen, mystics, artists, counselors, and scientists, if allowed to flourish, benefits not only women but also males. The following study examines the representation of women in fiction.